2008
DOI: 10.1074/jbc.m804925200
|View full text |Cite
|
Sign up to set email alerts
|

The Diversity of O-Linked Glycans Expressed during Drosophila melanogaster Development Reflects Stage- and Tissue-specific Requirements for Cell Signaling

Abstract: Appropriate glycoprotein O-glycosylation is essential for normal development and tissue function in multicellular organisms. To comprehensively assess the developmental and functional impact of altered O-glycosylation, we have extensively analyzed the nonglycosaminoglycan, O-linked glycans expressed in Drosophila embryos. Through multidimensional mass spectrometric analysis of glycans released from glycoproteins by ␤-elimination, we detected novel as well as previously reported O-glycans that exhibit developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
163
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(167 citation statements)
references
References 100 publications
4
163
0
Order By: Relevance
“…Drosophila also expresses these O-glycans on EGF-like repeats of Notch and other proteins. However, O-fucose glycans in Drosophila may have a glucuronic acid attached to the O-fucose (Aoki et al 2008), and there is no evidence for the addition of Gal or sialic acid to the GlcNAc (Xu et al 2007). C. elegans has protein O-fucosyltransferase 1 (Loriol et al 2006), but no close homologue of Fringe, the transferase that adds GlcNAc to Fucose-O-EGF (Bruckner et al 2000;Moloney et al 2000).…”
Section: O-glycosylationmentioning
confidence: 99%
“…Drosophila also expresses these O-glycans on EGF-like repeats of Notch and other proteins. However, O-fucose glycans in Drosophila may have a glucuronic acid attached to the O-fucose (Aoki et al 2008), and there is no evidence for the addition of Gal or sialic acid to the GlcNAc (Xu et al 2007). C. elegans has protein O-fucosyltransferase 1 (Loriol et al 2006), but no close homologue of Fringe, the transferase that adds GlcNAc to Fucose-O-EGF (Bruckner et al 2000;Moloney et al 2000).…”
Section: O-glycosylationmentioning
confidence: 99%
“…In flies, O-fucose on Notch has not been seen elongated past the GlcNAc␤1-3Fuc-O-Ser/Thr disaccharide by galactosyltransferases or sialyltransferases (23). However, in an O-glycomics analysis of total protein extracts from fly embryos, Aoki et al (27) reported a novel GlcNAc␤1-3(GlcA␤1-4)fucitol glycan. Interestingly, this trisaccharide was observed in Fringe-rich tissues during embryonic and larval stages of fly development when Notch is known to function (27).…”
mentioning
confidence: 99%
“…However, in an O-glycomics analysis of total protein extracts from fly embryos, Aoki et al (27) reported a novel GlcNAc␤1-3(GlcA␤1-4)fucitol glycan. Interestingly, this trisaccharide was observed in Fringe-rich tissues during embryonic and larval stages of fly development when Notch is known to function (27). Whether this O-fucose trisaccharide occurs on Notch remains to be resolved.…”
mentioning
confidence: 99%
“…The GlcNAc-␤1,3-Fuc disaccharide can be extended to a tetrasaccharide in mammals (16). A branched O-fucose trisaccharide (GlcUA-␤1,4-(GlcNAc-␤1,3)-Fuc) has been detected in total extracts of Drosophila larvae and wing discs, but it is not clear whether this modification is on EGF repeats of Notch (33). Elongation beyond the GlcNAc-␤1,3-Fuc disaccharide has not been detected on Drosophila Notch produced in S2 cells (34).…”
mentioning
confidence: 99%